The Effect Of Community Complaints Handling, Service Time Effectiveness And Service Quality On Community Satisfaction At The Office Of Dinas Kependudukan Dan Pencatatan Sipil Kota Kupang - Luis Marnisah Riwukore; Juhaini Alie; Yosef Ekliopas Ishak Rohi (Enrichment : Journal of Management, 2022)
The purpose of the study was specifically to obtain the results of the analysis of the effect of the variable handling of public complaints, the effectiveness of service time, and service quality on community satisfaction partially or simultaneously. The research method uses descriptive and verification surveys, and field data collection uses questionnaires, interviews, and documentation techniques. This research is associative research, where in this study there are variables that are related and can influence other variables. The population of this study was 2,103 people who visited and took care of population administration and civil registration documents at the Kupang City Population and Civil Registration Office. Based on the population, the sample was determined by purposive sampling using a probability of 10% from the Slovin respondent determination technique so that the sample of research respondents became 96 people. Processing data using SPSS 25 analysis tools. Testing data using t-test, that the handling of public complaints has an effect on community satisfaction with t-count 15.319 > t-table 1.98552, there is an effect of service time effectiveness on community satisfaction, with t-count 21.180 > t-table 1.98552, quality service affects the community satisfaction with t-count 2.159 > t-table 1.98552 and the handling of public complaints, the effectiveness of service time and service quality affect community satisfaction with F-count > F-table or 149.667 > 2.47. The common thread of research is that the handling of public complaints, the effectiveness of service time, and service quality have a positive and significant effect on community satisfaction at the Office of Dinas Kependudukan dan Pencatatan Sipil Kota Kupang, either partially or simultaneously.